Study on Microchannel Design and Burst Frequency Detection for Centrifugal Microfluidic System - Yaw-Jen Chang; Shia-Chung Chen; Cheng-Li Hsu (Advances in Materials Science and Engineering)
A centrifugal microfluidic system has been developed in this study, enabling the control and measurement of the burst frequency in order to manipulate the liquid. The radial microfluid chips with different microchannel dimensions were designed for simulation analyses and experimental verifications. The microfluidic flow in the microchannel was analyzed using software CFDRC, providing an accurate result compared with that from experiment. The results show that the design of the overflow microchannel can correctly keep the liquid volume with error as low as 5%. For mercurochrome, the burst frequency has an inverse proportion to the channel width, and the simulation results agree with the experimental results. For oil, however, the experimental and simulation results indicate that the relationship between the burst frequency and channel width is not obvious due to oil properties. Since the simulation approach can provide an accurate prediction of flow behavior in the microchannel, the design of radial microfluid chip and the control of burst frequency can be achieved effectively. A practical application to design the centrifugal microfluidic disc for blood typing test was also carried out in this study. The centrifugal microfluidic system can successfully control the spinning speed to achieve the result of adding reagents in a specific sequence.